2020
DOI: 10.1002/pmh.1497
|View full text |Cite
|
Sign up to set email alerts
|

Validity, reliability and hierarchical structure of the PID‐5 among Egyptian college students: Using exploratory structural equation modelling

Abstract: Background -The present study aimed to investigate the pathological personality traits of undergraduate students using the Personality Inventory for among Egyptian university-age participants. Method -We replicated the five-factor model of the PID-5 using exploratory structural equation modelling analysis with target rotation towards the original study of the PID-5 construction. Next, we estimated the factor congruence to identify the similarity of the present five-factor solution with the available relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
(108 reference statements)
2
6
0
1
Order By: Relevance
“…The reliability, internal consistency, and temporal stability indexes proved to be adequate, similar to the studies addressing the original English version [α ≥ 0.72; ( 4 )] and cross-cultural adaptations addressing general populations [α ≥ 0.68; r ≥ 0.56: ( 50 52 )]. However, the Suspiciousness facet is an exception because its internal consistency indicators were below the expected (α ≤ 0.69), a finding already reported by other studies ( 11 , 17 , 19 , 53 ).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The reliability, internal consistency, and temporal stability indexes proved to be adequate, similar to the studies addressing the original English version [α ≥ 0.72; ( 4 )] and cross-cultural adaptations addressing general populations [α ≥ 0.68; r ≥ 0.56: ( 50 52 )]. However, the Suspiciousness facet is an exception because its internal consistency indicators were below the expected (α ≤ 0.69), a finding already reported by other studies ( 11 , 17 , 19 , 53 ).…”
Section: Discussionmentioning
confidence: 53%
“…Divergences concern the Negative Affect domain, which grouped a more significant number of facets (Suspiciousness, Impulsivity, and Distractibility), and the Disinhibition domain, which was composed of only two of its original facets (Irresponsibility, Rigid Perfectionism). Regarding Negative Affect, previous studies have repeatedly shown the Suspiciousness' (Detachment) high factor loading in this domain ( 17 , 18 , 20 , 28 , 76 , 78 ). On the other hand, Lotfi et al ( 78 ) had already reported an association between the Impulsivity and Distractibility facets, which were initially linked to Disinhibition and Negative Affect.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations